A MARKETING - KEY FACTOR FOR PRODUCTIVITY OF THE ENTERPRISES IN THE MARKET ECONOMY - Alili, Erkan (International Scientific Journal Vision, 2018)
Marketing is one of the most important sectors on which all companies focus, regardless of their size or the activity they carry out. As a predisposition, marketing plays a major role in the business world and can be considered as a key element of the enterprises in planning for achieving maximum organizational productivity.The development of the production forces has led to an inc-rease in the level of productivity, while trade liberalization contributes to the increase of the competition on the market. From the marketing point of view, the market is classified as a component of marketing. The relationship between supply and demand is one of the key information essential to all companies and their success in theperformance. Entrants participating in the market have diff erent behaviors depending on their role as purchaser or seller. All of these characteristics infl uence in determining the direction of mo-vement towards the development of the market, which have a huge impact on the behavior of consumers. For more specific and more thorough planning, the Marketing Information System is of great importance. The decision-making process in the enterprises is a dynamic process based on the accumulated knowledge, the experience of the entities and the information gathered during the research. Being aware of the needs of the consumers creates space for designing superior products with an aff ordable price that will have quick realization.